Ultrasensitive Molecular Sensors Based on Real‐Time Impedance Spectroscopy in Solution‐Processed 2D Materials (Adv. Funct. Mater. 12/2022). (16th March 2022) - Moore, David C.; Jawaid, Ali; Busch, Robert; Brothers, Michael; Miesle, Paige; Miesle, Adam; Rao, Rahul; Lee, Jonghoon; Beagle, Lucas K.; Motala, Michael; Wallace, Shay Goff; Downing, Julia R.; et al.
Abstract : Ultrasensitive Molecular Sensors In article number 2106830, Nicholas R. Glavin and co‐workers describe a real‐time impedance spectroscopy approach, which enables ultrasensitive molecular sensors in solution processed 2D nanomaterials. Through bypassing traditionally dominant interflake interactions and selectively extracting intraflake doping effects, detection of NO2 vapor down to 1 ppb is readily achievable with an ultimate limit of detection approaching 63 ppt. Image by Dr. Jo Richers (www.jorichers.com).